Meningkatkan Aktivitas Memori Kerja Berbantuan Binaural Beats - Jatmika Nurhadi; Syihabuddin Syihabuddin (Pedagogi: Jurnal Ilmu Pendidikan, 2021)
This study aims to investigate the impact of providing binaural beats (BB) stimulus on working memory activity. This study used an experimental method using a one-time case study (one-chance case study). This study involved 30 respondents consisting of men and women aged 18-20 years. The participants will do two readings of different scientific articles with the same cognitive level. The first data collection was carried out without providing any stimulus, while the second data collection was carried out by providing a stimulus in the form of a BB with a frequency of 15Hz. Data were collected from the results of electroencephalographic recording (EEG) then processed using the EEG Lab to calculate the value of the Power Spectral Density (PSD). The average PSD value before and after the stimulus was calculated statistically by performing the Paired Sample T-Test. The results of this study indicate that there is a significant difference between the mean value of PSD before and after the stimulus is given. This shows that BB can have an impact on improving memory performance in reading scientific articles